Synthesis and biological evaluation of novel 2, 3-pyrazole ring-substituted-4, 4-dimethyl lithocholic acid derivatives as selective protein tyrosine phosphatase 1B (PTP1B) inhibitors with cellular efficacy. Issue 129 (15th December 2015) - Mao, Shi-Wei; Shuai, Lin; He, Hai-Bing; Pan, Na; Gao, Li-Xin; Yu, Li-Fang; Li, Jia; Li, Jing-Ya; Yang, Fan
Abstract : Fourteen 2, 3-pyrazole ring-substituted 4, 4-dimethyl lithocholic acid derivatives were designed and synthesized as novel PTP1B inhibitors with good potency, selectivity as well as cell permeability. Abstract : In our continued efforts to develop lithocholic acid (LCA) analogues as selective PTP1B inhibitors, 14 novel 2, 3-pyrazole ring-substituted-4, 4-dimethyl derivatives were synthesized and evaluated against PTP1B, as well as homologous protein tyrosine phosphatases (PTPs). All compounds were shown to be more potent and selective PTP1B inhibitors than LCA (IC50 = 12.74 μM) with IC50 values ranging between 0.42 to 4.49 μM. Moreover, treatment of CHO/hIR cells with 4, 4-dimethyl-2′-( p -fluoro phenyl)-2′ H -chola-2, 5-dieno[3, 2- c ]pyrazol-24-oic acid (30 ) or 4, 4-dimethyl-2′-( o -chloro phenyl)-2′ H -chola-2, 5-dieno[3, 2- c ]pyrazol-24-oic acid (34 ) increased the phosphorylation levels of IR and Akt in a dose dependent manner. The promising findings in this study suggest that further investigation of these compounds for the treatment of metabolic disorders is warranted.